Resistance to Dichelops melacanthus (Hemiptera: Pentatomidae) in soybean genotypes of different maturity groups - Canassa,Vinícius Fernandes (2017)
ABSTRACT Some species of pentatomids stink bugs have global economic importance, damaging various plant species during the vegetative and reproductive phases. Dichelops melacanthus (Dallas) (Hemiptera: Pentatomidae), known as the green-belly stink bug, is part of the soybean stink bug complex in Brazil and has increasing importance in crops,with potential to reduce crop yield. This polyphagous stink bug has been registered in 29 plant species belonging to 10 plant families which include cultivated and non-cultivated plants. Plant resistance is a valuable tool in integrated pest management and may reduce insect populations below economic injury level. This study characterized the resistance of 17 soybean genotypes to the green-belly stink bug. All of the materials affected the biological performance of the green-belly stink bug, but PI 227687; ‘IAC 100’; PI 171451; IAC 78-2318; D 75-10169; IAC 74-2832; ‘IAC 23’ and ‘IAC 24’ caused mortality above 80% in the second instar. ‘IAC 17’; ‘IAC 18’; PI 171451; PI 274454; ‘Conquista’ and ‘IAC 19’ decreased the longevity of adults of D. melacanthus, showing the same mechanism of resistance. PI 227687 did not allow any insects to complete the immature stage. These results are unprecedented for the species D. melacanthus and can assist breeding programs that focus on resistance to members of the stink bug complex in soybean.